2021
DOI: 10.1155/2021/5573471
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Sustained Attention by Theta-tACS over the Lateral and Medial Frontal Cortices

Abstract: Theta oscillations over the posterior medial frontal cortex (pMFC) and lateral prefrontal cortex (LPFC) play vital roles in sustained attention. Specifically, pMFC power and pMFC-LPFC synchronization correlate with cognitive control in sustained-attention-related tasks, but the causal relationships remain unknown. In the present study, we first analyzed the correlation between EEG theta oscillations (characterized by time-frequency power and phase-based connectivity) and the level of sustained attention (Exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The results showed that at least one cognitive function improved following tACS in all cognitive areas, which is largely consistent with the study hypothesis. tACS of 6 Hz and 1 mA for 15 min was applied to the left DLPFC of the subjects, and through the use of a psychomotor vigilance task (PVT) and EEG analysis, it was found that compared with the sham stimulation group, the phase synchronization of the θ band following stimulation was significantly reduced in the true stimulation group, thus adjusting the sustained attention in the cognitive domain [26]. Varastegan et al [27] also subjected 16 elderly individuals with subjective memory complaints (SMC) to 6 Hz tACS, evaluated and recorded using the Rey Auditory-Verbal Learning Test (RAVLT), and found that θ-tACS could improve cognitive components such as event memory in SMC patients through activity in the frontal and temporal regions of the brain.…”
Section: Application Of Tacs In the Cognitive Domainmentioning
confidence: 99%
“…The results showed that at least one cognitive function improved following tACS in all cognitive areas, which is largely consistent with the study hypothesis. tACS of 6 Hz and 1 mA for 15 min was applied to the left DLPFC of the subjects, and through the use of a psychomotor vigilance task (PVT) and EEG analysis, it was found that compared with the sham stimulation group, the phase synchronization of the θ band following stimulation was significantly reduced in the true stimulation group, thus adjusting the sustained attention in the cognitive domain [26]. Varastegan et al [27] also subjected 16 elderly individuals with subjective memory complaints (SMC) to 6 Hz tACS, evaluated and recorded using the Rey Auditory-Verbal Learning Test (RAVLT), and found that θ-tACS could improve cognitive components such as event memory in SMC patients through activity in the frontal and temporal regions of the brain.…”
Section: Application Of Tacs In the Cognitive Domainmentioning
confidence: 99%